Quality control issues for the roads of RHD; present state, challenges and scope of improvement - A. K. M. Shamsuzzoha (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.